A phase 2 study of fluorouracil/leucovorin in combination with paclitaxel and oxaliplatin as a salvage treatment in patients with refractory or relapsed advanced gastric cancer. (February 2015) - Lin, Rongbo; Fan, Nanfeng; Wu, Guangfeng; Chen, Ying; Guo, Zengqing; Wang, Xiaojie; Jin, Feng; Chen, Ling; Liu, Jie
<x content-type="archive" xml:space="preserve">Abstract</x> The aim of this study was to evaluate the efficacy and safety of paclitaxel plus oxaliplatin plus fluorouracil/leucovorin (POF) as salvage chemotherapy in pretreated advanced gastric cancer. Fifty-two pretreated patients with the advanced gastric cancer were eligible for this study. The POF regimen consisted of a 3-hour infusion of paclitaxel (135 mg/m2) followed by oxaliplatin (85 mg/m2) and leucovorin (400 mg/m2), administered simultaneously over a 2-hour infusion period, followed by an infusion of fluorouracil (2400 mg/m2) over a 46-hour period, every 14 days. From an intention-to-treat analysis, overall response rate and stable disease rate were 28·8 and 38·5%, respectively. The median time to progression and overall survival were 4·1 and 7·9 months, respectively. Grade 3 or 4 neutropaenia, thrombocytopaenia, fatigue, and neuropathy were 38·5, 15·4, 17·3, and 15·4%, respectively. The POF regimen is active in pretreated advanced gastric cancer as salvage chemotherapy, with a favourable toxicity profile.